2010
DOI: 10.1371/journal.pone.0008525
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity and Small-World in Mesial Temporal Lobe Epilepsy

Abstract: BackgroundThe functional architecture of the human brain has been extensively described in terms of functional connectivity networks, detected from the low–frequency coherent neuronal fluctuations that can be observed in a resting state condition. Little is known, so far, about the changes in functional connectivity and in the topological properties of functional networks, associated with different brain diseases.Methodology/Principal FindingsIn this study, we investigated alterations related to mesial tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
427
7
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 476 publications
(482 citation statements)
references
References 63 publications
44
427
7
4
Order By: Relevance
“…Functional magnetic resonance imaging (fMRI) during task‐free conditions has been widely used to portray functional network characteristics in both normal and pathological conditions [Seeley et al, 2009], including MTLE. Different studies have investigated the impact of MTLE on these resting state networks (RSNs) [Bettus et al, 2009; Cataldi et al, 2013; Haneef et al, 2014; Laufs et al, 2007; Liao et al, 2010], including analysis of specific networks such as the default mode network (DMN) and the salience network. [Zhang et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional magnetic resonance imaging (fMRI) during task‐free conditions has been widely used to portray functional network characteristics in both normal and pathological conditions [Seeley et al, 2009], including MTLE. Different studies have investigated the impact of MTLE on these resting state networks (RSNs) [Bettus et al, 2009; Cataldi et al, 2013; Haneef et al, 2014; Laufs et al, 2007; Liao et al, 2010], including analysis of specific networks such as the default mode network (DMN) and the salience network. [Zhang et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…These studies evaluated the relationships between the syndrome alterations and properties such as degree of connectivity, clustering coefficient and hub distribution, demonstrating alterations in MTLE characterized by reduced specificity and global efficiency [Bernhardt et al, 2011; Liao et al, 2010]. Most of the previous graph theory studies in MTLE have applied anatomical parcellation to functional maps and compared differences between right and left MTLE groups in comparison to controls [Bettus et al, 2009; Wang et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairments in patients with TLE have also been correlated with changes in functional connectivity (Vlooswijk et al, 2010;Waites et al, 2006;Zhang et al, 2009). Liao et al (2010) found both increases and decreases in resting-state functional connectivity in patients with TLE; two regions with significant decreases in connectivity displayed a negative correlation with the duration of epilepsy. Similar to observed changes in gray matter, alterations in connectivity appear in structures thought to be involved in seizure networks, suggesting a relationship between repeated seizure activity and functional connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Application of connectivity principles to these data has promoted research in various aspects of epileptic seizures, and there has been overwhelming report of decreased connectivity around the seizure-onset zone [2][3][4][5][6] and the default mode network (DMN) by several groups. 7,8 In 2012, Jehi 7 and Morgan et al 9 reported that connectivity patterns were different in patients with right and left mesial temporal sclerosis and that there was decreased connectivity between the regions of the DMN and the hippocampus and amygdala in patients with mesial temporal sclerosis. Similarly, hemispheric connectivity analysis in patients with unilateral mesial temporal sclerosis revealed decreased local and intrahemispheric connectivity and increased interhemispheric connectivity.…”
mentioning
confidence: 99%